Consumer Insights and the Importance of Competitiveness Factors for Mature and Developing Destinations. Issue 2 (3rd April 2017) - Wilde, Simon J.; Cox, Carmen; Kelly, Stephen J.; Harrison, Jennifer L.
ABSTRACT: This article aims to understand the importance of various destination attributes to the competitiveness of tourism destinations from a consumer perspective, while at the same time contrasting these in a mature versus developing destination. A sample of Australian-based domestic tourists were surveyed to assess the relative importance of tourism destination competitiveness (TDC) attributes in the context of developing and mature destinations. This research firstly appears to verify that the importance of many TDC elements, highlighted by consumers, is not dissimilar from other stakeholder-based TDC studies. Furthermore, this research effort established that in terms of attribute performance, relative destination immaturity may well constrain a developing destination's ability to satisfy the needs of consumers.